DO PROFITABILITY, LIQUIDITY, LEVERAGE, AND SALES GROWTH PREDICT FINANCIAL DISTRESS? EVIDENCE FROM CONSUMER GOODS FIRMS IN INDONESIA - Daud Sofyan Rachman; Tituk Diah Widajantie (ZILLZELL MEDIA PRIMA, 2026)
The growing number of enterprises in Indonesia's main consumer products industry has resulted in more strong commercial rivalry. As a result, firms must maintain consistent and long-term financial success. However, not all major consumer products firms manage their finances efficiently, making them subject to financial crisis. Using a purposive selection strategy, this research will examine profitability, liquidity, leverage, and sales growth indicators as predictors of financial distress in major consumer products industries from 2021 to 2024. The study was driven by increased business rivalry and diminishing earnings in some firms, which have the potential to cause financial issues. This study's research sample was generated using a purposive sampling strategy, including eight firms and four years of observation. The data was analysed using panel data regression in the E-Views 13 programme. The findings of this research show that profitability and liquidity have an impact on financial distress, however leverage and sales growth have no influence.